Analisis Nilai Perjuangan Tokoh Zainuddin dalam Novel Buya Hamka Tenggelamnya Kapal Van Der Wijk - Damariswara, Rian; Jadmiko, Rahmad Setyo (Universitas Muhammadiyah Surabaya, 2024)
The purpose of this study is to analyze the values ​​of the struggle of the Zainuddin character in Buya Hamka's novel Tenggelamnya Kapal Van Der Wijck. . This research directly collects information obtained from the object of research, namely the novel